ChemInform Abstract: Yttrium‐Catalyzed Addition of Benzylic C—H Bonds of Alkyl Pyridines to Olefins. Issue 35 (8th August 2013) - Guan, Bing‐Tao; Wang, Baoli; Nishiura, Masayoshi; Hou, Zhaomin
Abstract An excellent catalytic system for the ortho‐selective benzylic C—H addition of various dialkyl pyridines is presented.